A Miniaturized and High Optically Transparent Frequency Selective Surface for RF Shielding Using Double-Glazed Glass Windows for Green Building Applications - Muhammad Nasir; Slawomir Koziel; Adnan Iftikhar (IEEE Access)
This research presents a miniaturized and high optically transparent (OT) frequency selective surface (FSS) for achieving RF shielding through glass window panels. The proposed FSS consists of a single-layered copper pattern sandwiched between two ordinary glass substrates to suppress the dual bands of sub-6 fifth generation (5G). In particular, the design effectively shields n65-downlink (2.1 GHz) and a portion of n78-band (3.5 GHz). The unit cell (UC) design consists of square and butterfly rings with a maximum copper width of 0.1 mm. The dimensions of FSS unit cell (UC) are optimized to $0.0714λ _{0}× 0.07146λ _{0}$ , where $λ _{0}$ is the wavelength at 2.1 GHz resonant frequency. Full-wave electromagnetic (EM) simulations, equivalent circuit modeling (ECM), and experimental testing are performed to validate the FSS performance. The design miniaturization and 0.1 mm copper trace width offered a maximum OT of 91.6 % and angular stability up to ${85}^{^{° }}$ for both transverse electric (TE) and transverse magnetic (TM) polarized waves.